Populisme et gestion national-populaire du pouvoir en Bolivie : l’expérience du Mouvement nationaliste révolutionnaire – MNR– (1952-1964) - Christine Delfour (Amnis)
In Latin America, and more particularly in Bolivia, populism cannot be distinguished from nationalism. Nationalism prevails not only in periods of crisis, but it also contributes, throughout history, to the building of the nation, and to the making of a community of citizens that include underprivileged and Indians. Furthermore it is characterized by porosity and even fusion between the public and the private, which thrives on the traditional links of social reciprocity and State domination – and thus generates a specific mode of political management. The study of the “Nationalist Revolutionary Movement” (NRM) in Bolivia (1952-64) offers an example of the national populist process typical of that nation. It provides the opportunity to analyse the permanent features of the National-populist management of politics in Bolivia (I), to raise the issue of populism throughout Latin America (II), to identify the roots of the Nationalist Revolutionary Movement (III), and to give examples of public policies inspired by national populism (IV). During this period, we are faced, with the classical ambiguities of populism, but we also note that, in spite of its deficiencies and potential drifts, the national popular management, embodied by the NRM, invented by a new progressist generation, can also be considered as a transition, even a step, towards democracy.